2023
DOI: 10.1007/s10865-023-00400-2
|View full text |Cite
|
Sign up to set email alerts
|

Implementation strategies preferred by primary care clinicians to facilitate cancer prevention and control activities

Abstract: Key clinical and community members need to be involved in the identification of feasible and impactful implementation strategies for translation of evidence-based interventions into practice. While a wide range of implementation strategies has been developed, there is little research on their applicability for cancer prevention and control (CPC) efforts in primary care. We conducted a survey of primary care physicians to identify implementation strategies they perceive as most feasible and impactful. The surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The survey also focused on types of implementation strategies clinicians found most helpful. Ratings revealed that only one implementation strategy (adapt to my practice) was rated highly on both feasibility and estimated impact [ 66 ]. There were no differences associated with CPC topic, rural vs. urban setting, or clinician characteristics.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The survey also focused on types of implementation strategies clinicians found most helpful. Ratings revealed that only one implementation strategy (adapt to my practice) was rated highly on both feasibility and estimated impact [ 66 ]. There were no differences associated with CPC topic, rural vs. urban setting, or clinician characteristics.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The rates of smoking are higher in rural areas and people in rural and remote areas might experience more problems in accessing and following advice that is relevant to prevention [10,11]. Success largely depends on assessing whether needs differ among types of healthcare practice, and identifying the specific areas in preventive services where clinicians require the most improvement and assistance [12]. In the past decade, close to 100 new cancer medications have gained approval in Europe, but their availability is limited, with Central and Eastern European (CEE) countries notably trailing Northern and Western Europe.…”
Section: Introductionmentioning
confidence: 99%
“…While primary care prevention is widely recommended, delivering a variety of relevant services is often unfeasible for most clinicians, especially in low-resource and rural healthcare settings. The gap between research and practical implementation in cancer prevention and control, as in other preventive healthcare areas, is well-documented [15]. A study reports an average of 17 years for only 14% of research evidence to be put into practice.…”
Section: Introductionmentioning
confidence: 99%